The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1364/josaa.18.000265
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the human lens: changes in lens shape at zero-diopter accommodation

Abstract: Scheimpflug photographs of the zero-diopter-accommodated anterior segments of 100 human subjects, aged 18 to 70 yr and evenly spaced over this range, were digitized and analyzed to characterize lens and lens nucleus shape as a function of age by the Hough transform and other image analysis methods. Anterior and posterior lens surface curves exhibit a decrease in radius of curvature with increasing age, in qualitative but not quantitative agreement with the earlier observations of Brown [Exp. Eye Res. 19, 175 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…The width of the IA increased with decreasing patient age, which confirms age as a factor influencing the IA, as previous studies have reported [21,22]. The increase in crystalline lens volume with age seems to be crucial in this finding [23]. Likewise, our results suggest that the glaucoma mode evaluated is useful for quantitative evaluation of age-related changes in angle structure in healthy eyes.…”
Section: Discussionsupporting
confidence: 89%
“…The width of the IA increased with decreasing patient age, which confirms age as a factor influencing the IA, as previous studies have reported [21,22]. The increase in crystalline lens volume with age seems to be crucial in this finding [23]. Likewise, our results suggest that the glaucoma mode evaluated is useful for quantitative evaluation of age-related changes in angle structure in healthy eyes.…”
Section: Discussionsupporting
confidence: 89%
“…Clinical studies confirm that during accommodation the changes in position and curvature are larger in the anterior Hemenger et al (1995) 19-31 11.21 ± 1.08 6.45 ± 0.56 Phakometry Koretz et al (2001) 29 10.575 7.687 Scheimpflug Dubbelman and Van Der Heijde (2001) 29 11.247 5.852 Scheimpflug Garner and Yap (1997) 19-24 11.54 ± 1.27 6.62 ±0.94 Phakometry Dubbelman et al (2005) 29 11.8 6. It should be noted that in vitro the lens is in a different mechanical state of stress than in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…Although a Scheimpfl ug system could not compete in resolution with anterior segment optical coherence tomography (OCT), 15 which otherwise should also be corrected from optical distortion, 16,17 the large depth of focus in Scheimpfl ug images allows full cross-sections of the anterior segment, from the anterior cornea to the posterior lens, in a single snapshot generally not possible with OCT. Applications of corrected Scheimpfl ug crystalline lens/IOL in vivo imaging include customized eye modeling, 18,19 studies of quantitative changes of crystalline lens morphology with accommodation, 11,[20][21][22] aging, 6,23 or disease, 24 and assessment of new intraocular implants and surgical approaches for the correction of presbyopia. 25 …”
Section: Discussionmentioning
confidence: 99%